Awareness Of Physiotherapy Occupation In Education Of Patient Safety And Interprofessional Collaboration In Health Sciences: SWOT Analysis - Gizem Irem Kınıklı; Zafer Erden; Melih Elçin (Hacettepe University, 2015)
Objectives: The study was aimed to create simulation environment with developing new education programmes to increase the awareness of interprofessional collaboration and patient safety education in department of health sciences in Hacettepe University in 2010. Materials And Methods: Doctor candidates had courses about theoretical basic knowledge (28 hours), orthopedic clinic case examples based on empirical learning (4 hours), simulation interventions on standard patients with orthopedic clinical scenarios (28 hours) and solution meetings (4 hours) in the field of physiotherapy occupation. A questionnaire including questions about information, attitude, behaviour and awareness in the occupation of physiotherapist was applied 47 students at the beginning and the end of the education programme. Results: No statistically significant difference were found on answers to questions related to similar medical courses during bachelor education (p=0.219), having academic degrees (p=0.180), interventions related to patient safety (p=0.383), invasive practice (p=0.143) that demonstrated their awareness in the field of physiotherapy occupation. There were significant differences related to questions about intensive care employment (p<0.001), not have a responsibility of diagnosis (p=0.041), give an injection, or to take blood (p=0.007), radiography consultation and prescribe medicine (p<0.001) that indicated the strengths of the interprofessional collaboration and patient safety courses improved the awareness of the students. Conclusion: New education programmes and methods aimed simulation environments has to develop in the education of health professionals. In our country, this pilot study serves as a model in education in health sciences.